Manners in the Hikayat Musang Berjanggut - Abu Bakar, Roslina; Mamat, Siti Fatimah; Nik Muhamad Affendi, Nik Rafidah; Makmun, Rozaiman; Sujud, Arba’ie (Human Resource Management Academic Research Society, 2021)
This article focuses on the elements of politeness in Hikayat Musang Berjanggut (2007). Hikayat Musang Berjanggut is a humour story that is, in general, to function as entertaining and educating people. This is the opinion of Ismail (1986), which states that stories that come through Malay humour also bring various lessons and examples. The question that is presented through the Malay literary product is a depiction of the reality of life by the ruling system to be unraveled and made a guide in real life. Yet, the matter is against the opinion of Frank (1993: 17) states that the Malay community does not have a system or rule in the total daily life. His statement is clearly against the question that is posed through Hikayat Musang Berjanggut (2007) that proves that the Malay community since traditional times had systems with rules and practiced politeness in behavior. This study has two objectives. First, is to identify the politeness elements that is in the Hikayat Musang Berjanggut (2007). Secondly, to analyze the politeness elements based on the thinking framework of Syed (2001). This study uses the analysis of text method that refers to the Malay humor story titled Hikayat Musang Berjanggut (2007) and applies the Pendekatan Adab based on the thinking framework of Syed Naquib Al-Attas in the year 2001. The study results found that the Hikayat Musang Berjanggut is filled with politeness elements that describe human beings and ethics.